HUBUNGAN TINGKAT PENGETAHUAN DAN LAMA MENDERITA DIABETES MELLITUS (DM) DENGAN KEJADIAN ULKUS DIABETIKUM PADA PASIEN DM TIPE 2 - Ida Suryati; Def Primal; Darsis Pordiati (JURNAL KESEHATAN PERINTIS, 2019)
DM is a disease where the level of glucose (simple sugar) in high blood because the body cannot release or use insulin adequately. Type 2 diabetes can cause various chronic complications such as diabetic foot disorders. The number of DM patients in Bukittinggi Achmad Mochtar Hospital has increased in the last 2 years. In 2017 there are 1,350 DM patients, in 2018 there are 1,400 DM patients who visit the International Clinic. Information obtained from officers at the Achmad Mochtar Hospital International Police that officers did not provide health promotion about diabetic ulcers to DM patients who visited the internal poly. The purpose of the study was to determine the relationship level of knowledge and duration of suffering from diabetes with the incidence of diabetic ulcers. Descriptive analytic research method with cross sectional design. The population was all type 2 DM patients who visited the Bukittinggi Achmad Mochtar Hospital interne poly, with an average number of 117 people per month. The number of samples is 54 people, with sampling using accidental sampling. Data was processed and analyzed using the chi-square test. The results of univariate analysis showed that 72.2% of respondents had high level of knowledge, 61.1% had long suffered from DM and 79.6% had no diabetic ulcer. Bivariate results have a correlation between level of knowledge with the incidence of diabetic ulcer (p = 0,000) and there is a relationship between knowledge and incidence of diabetic ulcer (p = 0.036 and OR = 8.696). It was concluded that there was a relationship between level of knowledge and duration of suffering from diabetes with the incidence of diabetic ulcers. It is expected that the hospital management will make counseling information on diabetic ulcers for DM patients visiting the Bukittinggi Achmad Mochtar Hospital interne poly.